Phytoremediation potential of Landoltia punctata on petroleum hydrocarbons - (:unkn) unknown (My University, 2015)
0

In this study, the potential of Landoltia punctata for petroleum phytoremediation was evaluated. L. punctata was treated with diferent concentrations of Batman crude oil (BCO). Te plants were grown in nutrient solutions containing 0.5%, 1%, 2%, and 3% BCO by volume in a growth chamber for 7 days. Te fresh weight of the plants in the presence of BCO at a concentration of 0.5% v/v increased by 60% relative to the initial fresh weight. Furthermore, in comparison to the control, plant growth was retarded by 72% and 91% at concentrations of 2% and 3%, respectively. When plants were grown in media containing 0.5% BCO, more than 90% of C15 C25 n-alkane compounds were removed compared to the unplanted control (medium plus 0.5% BCO without plants). Pristane (Pr) and phytane (Ph) were both present in all samples, except in the experimental medium of 0.5% BCO application. On the other hand, Pr/Ph values obtained from all oil applications were not statistically diferent from those of the control samples. As a result, L. punctata could be used for the phytoremediation of fresh water resources contaminated with up to 1% crude oil.
Keywords: Biyoloji